Cooperative Teaching Technology in Primary Schools: Innovative and Integrative Methods - Abdullayevna, Kosimova (Indonesian Journal Publisher, 2025)
This article emphasises the importance of continuing reforms meant to raise the standard of education in our nation and incorporate cutting-edge technologies into the educational system. Both pedagogical theory and practice in the educational system are changing significantly in the modern day. Specifically, using cooperative learning strategies in elementary school classrooms improves learning while also fostering the growth of students’ abilities, memory, attention, and thinking. Furthermore, a pedagogical collaboration-based educational process promotes the social and personal growth of students. Through interactive techniques, cutting-edge technologies, and successful teacher-student interactions, the article highlights the importance of fostering students’ capacity for independent thought, creativity, and teamwork.